The Effect of Influencer Credibility and User Reviews on Skincare Purchase Decisions: Evidence from Shopee Users in Bogor - Rahman, Arif; Ariandi, Fajri; Arista, Roynaldi; Utama, Dani Chandra; Warsono (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the influence of influencer credibility and trust in user reviews on skincare purchasing decisions via social media. Addressing a gap in prior research that largely focuses on general consumer goods, it highlights the skincare sector’s unique characteristics of high involvement, personal preference, and perceived risk. Influencer credibility dimensions include expertise, honesty, sincerity, and engagement, while trust in user reviews is measured through the impact of positive/negative feedback and the credibility of information on product ingredients and long-term effects. Using a quantitative survey with purposive sampling, questionnaires were distributed to frequent skincare buyers on social media. Data were analyzed through multiple regression. Results indicate that influencer expertise and honesty significantly boost purchasing decisions, with engagement fostering trust indirectly. Positive user reviews emphasizing product ingredients and long-term effects also significantly influence decisions, underscoring the value of credible peer content. Findings align with previous studies on the role of credibility and trust in online purchasing but stress the skincare industry’s reliance on transparency and product efficacy. Practically, marketers should collaborate with knowledgeable influencers, ensure transparent communication, and encourage detailed user reviews. Future research should consider moderators like brand loyalty, price sensitivity, and perceived safety.